Die Verkündigung des Evangeliums nach Augustine allegorischer Auslegung von Ps 18(19),1–7 nebst ihrer Vor- und Wirkgeschichte - Sieben, Hermann Josef (Theologie und Philosophie, 2019)
Augustine, the most influential western Church Father and theologian, proclaimed tirelessly the Gospel. What was his theological concept of the Gospel proclamation? Particularly in two allegorical interpretations of Psalm 18:1–7 in his Enarrationes in Psalmos, but also in many other parts of his work, he gives a coherent and systematic answer to this question. A comparison with the pre-Augustinian interpretation of the mentioned verses reveals a substantial correspondence of his theological concept of Gospel proclamation with that of the early Christian argument from prophecy. A comparison with Cassiodor’s famous Commentary on the Psalms provides an example for its historical influence.